Large deformations in deep tunnels excavated in weak rocks: Study on Y-Basque high-speed railway tunnels in northern Spain - Cosimo Iasiello; Juan Carlos Guerra Torralbo; César Torrero Fernández (Underground Space, 2021)
Designing the support system for a deep tunnel in weak rock is always challenging, because a misjudgment of real rock behavior can lead to failures. During the construction of the Legutiano tunnel, which belongs to the high-speed railway network named Y-Basque in Spain, the measured convergences exhibited large deformations, which were significantly higher than those in the detailed design. At first glance, these deformations were associated with squeezing, as the tunnel was excavated in flysch-shales and limonite with a maximum cover of approximately 360 m. The aim of this study is to perform a retrofit analysis to compare the most popular empirical and analytical approaches for evaluating the squeezing effect, using geotechnical data pertaining to other tunnels excavated in the same area and in the same geological formations. Finally, a non-linear finite element analysis, focusing on time-dependent rock behavior, is conducted to reproduce the convergences measured.